OPPORTUNITY FOR USM ENGINEERING STUDENTS TO UNDERSTAND AND APPLY LEAN SIX SIGMA - MPRC, Pusat Media & Perhubungan Awam (USM, 2016)
USM, PENANG, 8 March 2016 Universiti Sains Malaysia (USM) recently signed a Memorandum of Agreement (MoA) with Bose Systems Malaysia Sdn. Bhd. for the continuation of the shortterm training for undergraduate students in Bose Lean Enterprise, similar to the training courses previously conducted.